What influences 11-year-olds to drink? Findings from the Millennium Cohort Study - Yvonne Kelly; Alice Goisis; Amanda Sacker; Noriko Cable; Richard G. Watt; Annie Britton (BMC, 2016)
Abstract Background Drinking in youth is linked to other risky behaviours, educational failure and premature death. Prior research has examined drinking in mid and late teenagers, but little is known about the factors that influence drinking at the beginning of adolescence. Objectives were: 1. to assess associations of parental and friends' drinking with reported drinking among 11 year olds; 2. to investigate the roles of perceptions of harm, expectancies towards alcohol, parental supervision and family relationships on reported drinking among 11 year olds. Methods Analysis of data from the UK Millennium Cohort Study on 10498 11-year-olds. The outcome measure was having drank an alcoholic drink, self-reported by cohort members. Results 13.6 % of 11 year olds reported having drank. Estimates reported are odds ratios and 95 % confidence intervals. Cohort members whose mothers drank were more likely to drink (light/moderate = 1.6, 1.3 to 2.0, heavy/binge = 1.8, 1.4 to 2.3). Cohort members whose fathers drank were also more likely to drink but these estimates lost statistical significance when covariates were adjusted for (light/moderate = 1.3, 0.9 to 1.9, heavy/binge = 1.3, 0.9 to 1.9). Having friends who drank was strongly associated with cohort member drinking (4.8, 3.9 to 5.9). Associated with reduced odds of cohort member drinking were: heightened perception of harm from 1-2 drinks daily (some = 0.9, 0.7 to 1.1, great = 0.6, 0.5 to 0.7); and negative expectancies towards alcohol (0.5, 0.4 to 0.7). Associated with increased odds of cohort member drinking were: positive expectancies towards alcohol (1.9, 1.4 to 2.5); not being supervised on weekends and weekdays (often = 1.2, 1.0 to 1.4); frequent battles of will (1.3, 1.1 to 1.5); and not being happy with family (1.2, 1.0 to 1.5). Conclusions Examining drinking at this point in the lifecourse has potentially important public health implications as around one in seven 11 year olds have drank, although the vast majority are yet to explore alcohol. Findings support interventions working at multiple levels that incorporate family and peer factors to help shape choices around risky behaviours including drinking.